Lipid Signaling During Gamete Maturation - Mostafa, Sherif; Nader, Nancy; Machaca, Khaled (Frontiers in Cell and Developmental Biology, 2022)
Cell lipids are differentially distributed in distinct organelles and within the leaflets of the bilayer. They can further form laterally defined sub-domains within membranes with important signaling functions. This molecular and spatial complexity offers optimal platforms for signaling with the associated challenge of dissecting these pathways especially that lipid metabolism tends to be highly interconnected. Lipid signaling has historically been implicated in gamete function, however the detailed signaling pathways involved remain obscure. In this review we focus on oocyte and sperm maturation in an effort to consolidate current knowledge of the role of lipid signaling and set the stage for future directions.